High-intensity specific intermittent training (SIT) in the preparation of the tennis player - Suárez Rodriguez, D.; Del Valle, M. (Archivos de medicina del deporte, 2018)
The ability to perform actions repeatedly at high speed has a very clear relationship with the manifestation of endurance in sports such as tennis. The training in which there are interspersed periods of work of high intensity with others of recovery turns out to be a type of training more specific than continuous type. Within the interval systems, the intermittent training of high intensity (Intermittent training-IT) suppose a specially suitable method to improve aerobic and anaerobic endurance. Through this training will we be able to act on the adaptations related to the recovery between points, which has a direct relationship with the performance in the matches. In addition, the high intensity and low volume of training allows an optimal synergy with qualities such as explosive force and speed, so important in sports in which periods of work and recovery are interspersed. However, tennis has some specific characteristics that differentiate it from other intermittent sports such as brief recoveries and techniques of displacement and hitting the ball, so the use of intermittent training using typical movements of tennis (Specific Intermittent Training-SIT) is an especially suitable system. The choice of the intensity of the effort of the relationship between work and recovery times, and the degree of skill of the player are determining factors when carrying out specific training at high intensity.